(untitled) (Libellarium: journal for research in the field of information and related sciences, 2014)
This paper analyses the nomenclature basis of publishing activities in the Republic of Croatia and the EU, and deals with the challenges of future comparative studies dealing with the structure of classifications. Creative and cultural industries are trying to find the optimal classification to define, track and direct creative/cultural activities. In some EU countries, the classification frames are in line with the stated classification, although some countries are still searching for nomenclature solutions. Studies of the nomenclature structure of cultural and creative industry are being conducted, and some of them are the framework of this paper (ESSnet – Culture 2011 and 2012). The publishing activity is classified according to the National Classification of Activities of the Republic of Croatia (NKD 2007 – The Official Gazette of the Republic of Croatia 58/2007) as class 58, and related activities are also classified: “book publishing” (58.11), “publishing of address books and lists of users’ addresses” (58.12), “publishing of newspapers” (58.13), “publishing of magazines and periodic publications” (58.14), “other publishing activities” (58.15).